Proton exchange membrane and preparation method and application thereof

The proton exchange membrane with a functional layer of proton conductive and absorbent materials addresses the limitations of traditional membranes by improving selectivity and mechanical strength while maintaining low ion conductivity, thus enhancing battery performance and longevity.

CN119725591APending Publication Date: 2025-03-28SHAANXI CANCN ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821114.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional proton exchange membranes in liquid flow batteries face issues such as low hydrogen ion selectivity, cross-contamination of positive and negative electrode ions, safety concerns, and high costs, which are not adequately addressed by increasing membrane thickness.

Method used

A proton exchange membrane with a functional layer comprising proton conductive materials and proton absorbent agents, such as graphene or carbon nanotubes, applied to the base membrane, enhancing selectivity and mechanical strength while minimizing impact on ion conductivity.

Benefits of technology

The proposed membrane design improves hydrogen ion selectivity, reduces ion cross-contamination, increases mechanical strength, and maintains low ion conductivity, thereby enhancing battery performance and longevity while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725591A_ABST
    Figure CN119725591A_ABST
Patent Text Reader

Abstract

The invention relates to a proton exchange membrane for a flow battery as well as a preparation method and application of the proton exchange membrane. The proton exchange membrane comprises a base material membrane and a functional layer arranged on at least one side surface of the base material membrane, the functional layer comprises a proton conduction base material and a proton adsorbent. According to the proton exchange membrane, the functional layer comprising the proton conduction base material and the proton adsorbent is arranged on the surface of the base material membrane, so that the selectivity of the membrane to hydrogen ions can be effectively improved, cross contamination of positive and negative vanadium ions is reduced, and the puncture strength of the membrane is enhanced; and the functional layer has very low influence on the ionic conductivity of the diaphragm in the use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a proton exchange membrane and a preparation method and application thereof. Background Art

[0002] Battery technology is one of the important energy supply methods that is indispensable in modern society. As a special type of battery, flow battery is widely used in large-scale energy storage systems due to its advantages such as high energy density, long cycle life and high safety. One of the core components of flow battery is proton exchange membrane (PEM), which plays the role of isolating positive and negative electrode electrolytes and conducting protons. The performance of proton exchange membrane directly affects the performance and service life of flow battery. Researchers in the fields of materials science and electrochemical engineering have been exploring ways to improve the performance of proton exchange membrane. Among them, perfluorosulfonic acid proton exchange membrane (PFSA PEM) has become a commonly used proton exchange membrane type in flow batteries due to its excellent chemical stability and conductivity. However, PFSA PEM also has some problems, such as low selectivity for hydrogen ions, easy cross-contamination of positive and negative vanadium ions, insufficient safety during use, and high cost.

[0003] In traditional technology, the ion selectivity of the diaphragm is enhanced by increasing the thickness of the diaphragm, suppressing the permeability of vanadium ions, thereby reducing the cross-contamination of vanadium ions between the positive and negative electrodes, while enhancing the mechanical strength of the diaphragm and improving safety during use. Although increasing the thickness of the diaphragm can improve the problem of poor ion selectivity of the diaphragm to a certain extent, there are still some problems. For example, although increasing the thickness of the diaphragm enhances the selectivity of the diaphragm, it also increases the surface resistance of the diaphragm; and increasing the thickness of the diaphragm is not conducive to reducing the cost of the diaphragm.

[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention

[0005] Based on this, the present application provides a proton exchange membrane and its preparation method and application, which not only improves the selectivity of the membrane to hydrogen ions, reduces the cross-contamination of positive and negative electrode vanadium ions, but also enhances the puncture strength of the membrane, and has very little impact on the conductivity of the membrane.

[0006] This application is implemented through the following technical solutions:

[0007] A first aspect of the present application provides a proton exchange membrane, which includes a substrate membrane and a functional layer provided on at least one surface of the substrate membrane; the functional layer includes a proton conductive substrate and an enhancer.

[0008] The proton exchange membrane in the present application includes a substrate membrane and a functional layer provided on at least one side of the substrate membrane, and the functional layer includes a proton conductive substrate and a proton adsorbent. The functional layer including the proton conductive substrate and the proton adsorbent is provided on the surface of the substrate membrane, which can not only effectively improve the selectivity of the diaphragm for hydrogen ions and reduce the cross contamination of vanadium ions of the positive and negative electrodes, but also has the effect of enhancing the puncture strength of the diaphragm, and the functional layer has a very low effect on the ionic conductivity of the diaphragm during use.

[0009] In one embodiment, the substrate membrane includes at least one of a perfluorosulfonic acid proton exchange membrane, a sulfonated polyetheretherketone proton exchange membrane, and a sulfonated polyimide proton exchange membrane;

[0010] and / or, the proton conductive substrate comprises at least one of polyaniline, polypyrrole and polythiophene;

[0011] And / or, the proton adsorbent includes at least one of graphene, carbon nanotubes, and carbon nanospheres.

[0012] In one embodiment, the mass ratio of the proton conductive substrate to the proton adsorbent is 5-7:3-5.

[0013] In one embodiment, the proton exchange membrane satisfies at least one of the conditions (1) to (4):

[0014] (1) The thickness of the substrate film is 8 μm to 135 μm;

[0015] (2) The particle size of the proton conductive substrate is 35 nm to 500 nm;

[0016] (3) The particle size of the proton adsorbent is 200 mesh to 5000 mesh;

[0017] (4) The thickness of the functional layer is 10 μm to 300 μm.

[0018] A second aspect of the present application provides a method for preparing a proton exchange membrane, comprising the following steps:

[0019] The proton conductive substrate, the proton adsorbent and the solvent are mixed to prepare a mixed slurry;

[0020] The mixed slurry is loaded on a substrate membrane and dried to prepare a proton exchange membrane.

[0021] In one embodiment, the preparation method satisfies at least one of the conditions (1) to (3):

[0022] (1) Based on the total mass of the mixed slurry, the mass fraction of the proton conductive substrate and the proton adsorbent is 5% to 25%;

[0023] (2) The solvent includes at least one of hydrochloric acid, phosphoric acid and sulfuric acid;

[0024] (3) The loading method includes spin coating, drip coating, spray coating or scraping coating.

[0025] In one embodiment, the process conditions of the spin coating are: the spin coating temperature is 25° C. to 85° C., the spin coating time is 20 s to 300 s, and the spin coating speed is 100 r / min to 1500 r / min.

[0026] In one embodiment, the drying temperature is 30° C. to 110° C., and the drying time is 0.5 h to 5 h.

[0027] The third aspect of the present application also provides an application of the above-mentioned proton exchange membrane in a liquid flow battery.

[0028] A fourth aspect of the present application further provides a liquid flow battery, which includes a cathode assembly, an anode assembly, and a proton exchange membrane as described above or a proton exchange membrane prepared by the above-mentioned proton exchange membrane preparation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the structure of the proton exchange membrane prepared in Example 1.

[0030] Description of reference numerals:

[0031] 10. proton exchange membrane; 100. substrate membrane; 200. functional layer. DETAILED DESCRIPTION

[0032] For ease of understanding of the present application, the present application will be described more fully below, and preferred embodiments of the present application are provided. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0033] The implementation of this application is described in detail below in combination with some implementation methods and examples. This example is implemented based on the technical solution of this application, and provides a detailed implementation method and specific operation process, but the protection scope of this application is not limited to the following examples.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0035] the term

[0036] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0037] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0038] In the present application, the terms "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0039] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0040] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0041] In this application, unless otherwise specified, the temperature parameter is allowed to be either a constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0042] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 2~5h means that the units of the left endpoint "2" and the right endpoint "5" are both h (hours).

[0043] See also Figure 1 In one embodiment of the present application, a proton exchange membrane 10 is provided. The proton exchange membrane 10 includes a substrate membrane 100 and a functional layer 200 disposed on at least one side of the substrate membrane 100. The functional layer 200 includes a proton conductive substrate and a proton adsorbent.

[0044] The proton exchange membrane 10 for liquid flow battery in the present application includes a substrate membrane 100 and a functional layer 200 arranged on the surface of at least one side of the above-mentioned substrate membrane 100, and the functional layer 200 includes a proton conductive substrate and a proton adsorbent. The functional layer 200 including the proton conductive substrate and the proton adsorbent is arranged on the surface of the substrate membrane, which can not only effectively improve the selectivity of the diaphragm for hydrogen ions and reduce the cross-contamination of vanadium ions between the positive and negative electrodes, but also has the effect of enhancing the puncture strength of the diaphragm, and the functional layer has a very low effect on the ionic conductivity of the diaphragm during use.

[0045] In some embodiments, the substrate membrane 100 includes at least one of a perfluorosulfonic acid proton exchange membrane, a sulfonated polyetheretherketone proton exchange membrane, and a sulfonated polyimide proton exchange membrane.

[0046] In some embodiments, the proton conductive substrate includes at least one of polyaniline, polypyrrole and polythiophene.

[0047] In some embodiments, the mass ratio of the proton conductive substrate to the proton adsorbent is 5-7:3-5.

[0048] It can be understood that when the mass of the proton adsorbent is relatively low, the proton conduction of the proton exchange membrane mainly depends on the proton conductive substrate. At this time, the proton conduction channel of the proton conductive substrate is relatively unobstructed, and protons can migrate between the acidic functional groups (such as sulfonic acid groups, etc.) or other conductive sites inside it. If a small amount of proton adsorbent can be evenly dispersed, it may serve as a supplementary proton conduction site to slightly increase the proton conductivity. For example, certain functional groups on the surface of the proton adsorbent (such as carboxyl, hydroxyl, etc.) can adsorb protons and form proton-enriched areas locally, promoting the transfer of protons between the conductive substrate and the adsorbent, and slightly accelerating the proton conduction. As the mass ratio of the proton adsorbent increases, the proportion of the proton adsorbent in the membrane increases. If the proton adsorbent can effectively adsorb and release protons and has a good synergistic effect with the proton conductive substrate, the proton conductivity may be significantly improved. Proton adsorbents can enrich protons in large quantities, forming a high-concentration proton region around them. When the proton concentration in the proton conductive substrate is low, these enriched protons can quickly diffuse to the conductive substrate, forming a proton gradient and accelerating the conduction of protons. However, if there are too many proton adsorbents, the proton conduction channel may be blocked, especially when the adsorbent agglomerates or has poor compatibility with the conductive substrate, the proton conductivity will decrease instead.

[0049] In some embodiments, the proton adsorbent includes at least one of graphene, carbon nanotubes and carbon nanospheres.

[0050] It can be understood that the above materials all have the effect of enriching hydrogen ions and can promote the conduction of hydrogen ions.

[0051] In a specific example, the proton adsorbent is graphene.

[0052] It can be understood that graphene has the effect of enriching hydrogen ions and promoting the conduction of hydrogen ions. When the graphene content in the mass ratio of proton conductive substrate to graphene is low, the proton exchange membrane mainly relies on the proton conductive substrate for proton conduction. At this time, graphene can be evenly dispersed, which can increase the diversity of proton conduction channels to a certain extent. As the mass ratio of graphene increases, the proportion of graphene in the proton exchange membrane increases. If graphene can cooperate well with the proton conductive substrate, its high specific surface area and excellent electrical properties can greatly improve the proton conduction performance. Graphene can promote the transport of protons through its own π-π conjugated system and surface functional groups (such as hydroxyl and carboxyl groups in graphene oxide). However, if graphene agglomerates in the membrane, it will hinder the proton conduction channel and cause a decrease in proton conductivity. Because the agglomerated graphene will occupy the space between the proton conductive substrates, reducing the effective channels for proton conduction.

[0053] In addition, a small amount of graphene can act as a reinforcing phase, which can improve the tensile strength and toughness of the membrane to a certain extent. For example, the high modulus characteristics of graphene can share part of the tensile stress, prevent the membrane from easily cracking during the stretching process, and improve the mechanical stability of the membrane. When the mass ratio of graphene increases, its effect on the mechanical properties of the proton exchange membrane is more significant. Since graphene has excellent mechanical properties (such as high Young's modulus), the overall stiffness of the membrane can be increased. However, if the interface between graphene and the proton conductive substrate is not well bonded, when subjected to external forces, stress concentration is easily generated at the interface, resulting in a decrease in the mechanical properties of the membrane.

[0054] In a specific example, the mass ratio of the proton conductive substrate to the proton adsorbent is 5-7:5.

[0055] Further controlling the mass ratio of the proton conductive substrate to the proton adsorbent within the above range, the proton exchange membrane has better selectivity and puncture strength for hydrogen ions and has a lower impact on the conductivity of the diaphragm.

[0056] In some embodiments, the thickness of the substrate film 100 is 8 μm-135 μm.

[0057] In some embodiments, the particle size of the proton conductive substrate is 35 nm to 500 nm.

[0058] It is understandable that the particle size of the proton conductive substrate will affect the proton conductive channel formed in the proton exchange membrane. The proton conductive substrate with a smaller particle size can be more evenly dispersed in the membrane to form a denser and more continuous proton conductive channel, which is conducive to the rapid transmission of protons, thereby improving the proton conductivity of the proton exchange membrane. On the contrary, the proton conductive substrate with a larger particle size may cause the discontinuity of the proton conductive channel to increase, reduce the transmission efficiency of protons, and reduce the proton conductivity. The particle size of the proton conductive substrate will also affect the mechanical strength and flexibility of the proton exchange membrane. The proton conductive substrate with a smaller particle size can be better filled in the structure of the membrane, increase the density of the membrane, and improve the mechanical strength of the membrane. At the same time, the proton conductive substrate with a smaller particle size can also make the membrane have better flexibility, so that it can better withstand mechanical stress during use and is not prone to rupture or damage. On the contrary, the proton conductive substrate with a larger particle size may cause the structure of the membrane to be uneven, reducing the mechanical strength and flexibility of the membrane.

[0059] In some embodiments, the particle size of the proton adsorbent is 200 mesh to 5000 mesh.

[0060] It can be understood that when the particle sizes of the proton conductive substrate and the proton adsorbent are appropriate, the smaller proton adsorbent particles can be filled in the particle gaps of the proton conductive substrate. For example, if the proton conductive substrate is a polymer microsphere with a certain particle size, and the proton adsorbent has a smaller particle size, it can be embedded in the gaps between these microspheres, and together with the substrate, it can build a more continuous and effective proton conductive channel. This tightly packed structure facilitates the migration of protons in the membrane and improves the proton conductivity. From a microscopic perspective, the appropriate particle size can make the lamellar structure of the proton adsorbent interact better with the molecular chain or particle surface of the proton conductive substrate. For example, the functional groups (such as hydroxyl, carboxyl, etc.) on the lamellar layer of the proton adsorbent can be close to the proton conductive groups (such as sulfonic acid groups) on the proton conductive substrate, forming a "relay" path for proton conduction, which promotes the rapid transmission of protons in the membrane. When the particle size of the proton adsorbent and the particle size of the proton conductive substrate are adapted to each other, such as synergy at the nanoscale, the proton adsorbent can be evenly dispersed in the proton conductive substrate like a "nano-enhanced phase". When subjected to external forces, the sheet of the proton adsorbent can withstand and disperse part of the stress, and the interaction with the proton conductive substrate can prevent the expansion of cracks, thereby improving the tensile strength and toughness of the proton exchange membrane 10. This structure can effectively resist the stress generated by the expansion or contraction of the electrode during the operation of the fuel cell, reducing the risk of membrane rupture.

[0061] In some embodiments, the thickness of the functional layer 200 is 10 μm-300 μm.

[0062] The gain effect of the above-mentioned functional layer can effectively reduce the thickness requirement of the diaphragm, thereby reducing the cost of the diaphragm, which is of great economic significance for large-scale production.

[0063] An embodiment of the present application further provides a method for preparing a proton exchange membrane 10, comprising steps S10 to S20.

[0064] Step S10: Mixing the proton conductive substrate, the proton adsorbent and the solvent to prepare a mixed slurry.

[0065] In some of the embodiments, based on the total mass of the mixed slurry, the mass fraction of the proton conductive substrate and the proton adsorbent is 5% to 25%.

[0066] In some embodiments, the solvent includes at least one of hydrochloric acid, phosphoric acid and sulfuric acid.

[0067] Step S20 : ​​loading the mixed slurry onto the substrate membrane 100 and drying the mixed slurry to prepare the proton exchange membrane 10 .

[0068] In some embodiments, the above-mentioned loading method includes spin coating, drop coating, spray coating or blade coating.

[0069] It can be understood that, according to the design, a single-sided coated diaphragm or a double-sided coated diaphragm can be prepared. This diverse process selection makes the technical solution of the present application widely adaptable and can meet different usage scenarios.

[0070] In some of the embodiments, the process conditions of the spin coating are as follows: the spin coating temperature is 25° C. to 85° C., the spin coating time is 20 s to 300 s, and the spin coating speed is 100 r / min to 1500 r / min.

[0071] In some embodiments, the drying process is carried out at a temperature of 30°C to 110°C.

[0072] In some embodiments, the drying time is 0.5 h to 5 h.

[0073] The method for preparing the proton exchange membrane for the liquid flow battery is simple to operate and process, and the prepared proton exchange membrane can meet the requirements of practical applications.

[0074] One embodiment of the present application also provides the application of the above-mentioned proton exchange membrane 10 for liquid flow battery in a liquid flow battery.

[0075] One embodiment of the present application also provides a liquid flow battery, which includes a cathode assembly, an anode assembly and the above-mentioned proton exchange membrane 10 for liquid flow battery or a proton exchange membrane 10 for liquid flow battery prepared by the preparation method of the above-mentioned proton exchange membrane 10 for liquid flow battery.

[0076] The above-mentioned liquid flow battery includes the above-mentioned proton exchange membrane 10, which can effectively improve the selectivity of the membrane to hydrogen ions, reduce the cross-contamination of positive and negative electrode vanadium ions, and greatly improve the performance and service life of the liquid flow battery.

[0077] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

[0078] In order to better illustrate the present application, the contents of the present application are further described below in conjunction with embodiments.

[0079] The present application is further described below in conjunction with specific embodiments, but they should not be construed as limiting the scope of protection of the present application.

[0080] Example 1

[0081] Step 1: Select a 50 μm thick perfluorosulfonic acid membrane (model N212, purchased from Suzhou Kerun New Materials Co., Ltd.) as the substrate membrane.

[0082] Step 2: Select a polyaniline:graphene mass ratio of 7:3 as the coating slurry, wherein the particle size of the polyaniline is 50 nanometers and the particle size of the graphene is 5000 mesh. Dissolve the polyaniline in a hydrochloric acid solution with a concentration of 1 mol / L to prepare a polyaniline and graphene mixed solution with a mass fraction of 10% to prepare a mixed slurry.

[0083] Step 3: In this embodiment, a spin coating process is selected for coating. The specific parameters of the spin coating process are: the spin coating temperature is 25° C., the spin coating time is 30 seconds, and the spin coating speed is 1000 rpm.

[0084] Step 4: Control the thickness of the coating by adjusting the spin coating time of the spin coating process. In this embodiment, the thickness of the functional layer is controlled at 30 microns.

[0085] Step 5: Place the perfluorosulfonic acid diaphragm coated with the mixed slurry in a vacuum drying oven and dry it at 60° C. for 2 hours to prepare a composite material.

[0086] Step 6: Place the dried composite material in an environment of 30° C. and 75% air humidity for 24 hours to prepare a proton exchange membrane for a liquid flow battery.

[0087] Step 7: Performance testing.

[0088] Example 2

[0089] Step 1: Select a 50 μm thick perfluorosulfonic acid membrane (model N212, purchased from Suzhou Kerun New Materials Co., Ltd.) as the substrate membrane.

[0090] Step 2: Select a polyaniline:graphene mass ratio of 5:5 as the coating slurry, wherein the particle size of the polyaniline is 50 nanometers and the particle size of the graphene is 5000 mesh. Dissolve the polyaniline in a hydrochloric acid solution with a concentration of 1 mol / L to prepare a polyaniline and graphene mixed solution with a mass fraction of 10% to prepare a mixed slurry.

[0091] Step 3: In this embodiment, a spin coating process is selected for coating. The specific parameters of the spin coating process are: the spin coating temperature is 25° C., the spin coating time is 30 seconds, and the spin coating speed is 1000 rpm.

[0092] Step 4: Control the thickness of the coating by adjusting the spin coating time of the spin coating process. In this embodiment, the thickness of the functional layer is controlled at 30 microns.

[0093] Step 5: Place the perfluorosulfonic acid diaphragm coated with the mixed slurry in a vacuum drying oven and dry it at 60° C. for 2 hours to prepare a composite material.

[0094] Step 6: Place the dried composite material in an environment of 30° C. and 75% air humidity for 24 hours to prepare a proton exchange membrane for a liquid flow battery.

[0095] Step 7: Performance testing.

[0096] Example 3

[0097] Step 1: Select a 50 μm thick perfluorosulfonic acid membrane (model N212, purchased from Suzhou Kerun New Materials Co., Ltd.) as the substrate membrane.

[0098] Step 2: Select a polyaniline:graphene mass ratio of 6:4 as the coating slurry, wherein the particle size of the polyaniline is 50 nanometers and the particle size of the graphene is 5000 mesh. Dissolve the polyaniline in a hydrochloric acid solution with a concentration of 1 mol / L to prepare a polyaniline and graphene mixed solution with a mass fraction of 10% to prepare a mixed slurry.

[0099] Step 3: In this embodiment, a spin coating process is selected for coating. The specific parameters of the spin coating process are: the spin coating temperature is 25° C., the spin coating time is 30 seconds, and the spin coating speed is 1000 rpm.

[0100] Step 4: Control the thickness of the coating by adjusting the spin coating time of the spin coating process. In this embodiment, the thickness of the functional layer is controlled at 30 microns.

[0101] Step 5: Place the perfluorosulfonic acid diaphragm coated with the mixed slurry in a vacuum drying oven and dry it at 60° C. for 2 hours to prepare a composite material.

[0102] Step 6: Place the dried composite material in an environment of 30° C. and 75% air humidity for 24 hours to prepare a proton exchange membrane for a liquid flow battery.

[0103] Step 7: Performance testing.

[0104] Example 4

[0105] The preparation methods of the proton exchange membranes of Example 4 and Example 1 are basically the same, the only difference being that the mass ratio of polyaniline:graphene is different, specifically, the mass ratio of polyaniline:graphene is 3:7.

[0106] Other conditions and parameters are the same as those in Example 1. Please see Table 1 for specific test results.

[0107] Example 5

[0108] The preparation methods of the proton exchange membranes of Example 5 and Example 1 are basically the same, the only difference being the type of the proton conductive substrate, specifically polypyrrole.

[0109] Other conditions and parameters are the same as those in Example 1. Please see Table 1 for specific test results.

[0110] Example 6

[0111] The preparation methods of the proton exchange membranes of Example 6 and Example 1 are basically the same, the only difference being the type of the proton conductive substrate, specifically polythiophene.

[0112] Other conditions and parameters are the same as those in Example 1. Please see Table 1 for specific test results.

[0113] Example 7

[0114] The preparation methods of the proton exchange membranes of Example 7 and Example 1 are basically the same, the only difference being the type of the proton conductive substrate, specifically carbon nanotubes.

[0115] Other conditions and parameters are the same as those in Example 1. Please see Table 1 for specific test results.

[0116] Comparative Example 1

[0117] The preparation methods of the proton exchange membranes of Comparative Example 1 and Example 1 are basically the same, except that no functional layer treatment is performed.

[0118] Other conditions and parameters are the same as those in Example 1. Please see Table 1 for specific test results.

[0119] Performance Testing

[0120] 1. The proton exchange membranes for flow batteries prepared in the examples and comparative examples were subjected to VO2 + Permeability test, the test method is in accordance with NB / T 42080-2023.

[0121] 2. The conductivity of the proton exchange membranes for flow batteries prepared in the examples and comparative examples was tested in accordance with NB / T 42080-2023.

[0122] 3. The proton exchange membranes for flow batteries prepared in the examples and comparative examples were subjected to puncture strength tests, and the test method was in accordance with GB / T6672-2001.

[0123] Table 1

[0124]

[0125] VO2 of the proton exchange membrane in Examples 1 to 7 and Comparative Example 1 + The permeability, conductivity and puncture strength are shown in Table 1. It can be seen that the proton exchange membrane prepared in the present application has better selectivity for hydrogen ions and puncture strength than the proton exchange membrane prepared in the comparative example, and has a lower impact on the conductivity of the diaphragm. The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-mentioned embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0126] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A proton exchange membrane, characterized in that: The proton exchange membrane comprises a substrate membrane and a functional layer arranged on at least one surface of the substrate membrane; the functional layer comprises a proton conductive substrate and a proton adsorbent.

2. The proton exchange membrane according to claim 1, characterized in that The substrate membrane comprises at least one of a perfluorosulfonic acid proton exchange membrane, a sulfonated polyetheretherketone proton exchange membrane and a sulfonated polyimide proton exchange membrane; and / or, the proton conductive substrate comprises at least one of polyaniline, polypyrrole and polythiophene; And / or, the proton adsorbent includes at least one of graphene, carbon nanotubes and carbon nanospheres.

3. The proton exchange membrane according to claim 1, characterized in that The mass ratio of the proton conductive substrate to the proton adsorbent is 5-7:3-5.

4. The proton exchange membrane according to any one of claims 1 to 3, characterized in that The proton exchange membrane satisfies at least one of the conditions (1) to (4): (1) The thickness of the substrate film is 8 μm to 135 μm; (2) The particle size of the proton conductive substrate is 35 nm to 500 nm; (3) The particle size of the proton adsorbent is 200 mesh to 5000 mesh; (4) The thickness of the functional layer is 10 μm to 300 μm.

5. A method for preparing a proton exchange membrane, characterized in that: The following steps are involved: The proton conductive substrate, the proton adsorbent and the solvent are mixed to prepare a mixed slurry; The mixed slurry is loaded on a substrate membrane and dried to prepare a proton exchange membrane.

6. The method for preparing a proton exchange membrane according to claim 5, characterized in that: The preparation method satisfies at least one of the conditions (1) to (3): (1) Based on the total mass of the mixed slurry, the mass fraction of the proton conductive substrate and the proton adsorbent is 5% to 25%; (2) The solvent includes at least one of hydrochloric acid, phosphoric acid and sulfuric acid; (3) The loading method includes spin coating, drip coating, spray coating or scraping coating.

7. The method for preparing a proton exchange membrane according to claim 6, characterized in that: The process conditions of the spin coating are as follows: the temperature of the spin coating is 25° C. to 85° C., the time of the spin coating is 20s to 300s, and the rotation speed of the spin coating is 100 r / min to 1500 r / min.

8. The method for preparing a proton exchange membrane according to claim 6, characterized in that: The temperature of the drying treatment is 30° C. to 110° C., and the time of the drying treatment is 0.5 h to 5 h.

9. Use of the proton exchange membrane according to any one of claims 1 to 4 in a liquid flow battery.

10. A liquid flow battery, characterized in that: The liquid flow battery comprises a cathode assembly, an anode assembly and a proton exchange membrane as claimed in any one of claims 1 to 4 or a proton exchange membrane prepared by the method for preparing a proton exchange membrane as claimed in any one of claims 5 to 9.